Cultural Transmission of Fine-Scale Fidelity to Feeding Sites May Shape Humpback Whale Genetic Diversity in Russian Pacific Waters. (3rd September 2018) - Richard, Gaëtan; Titova, Olga V; Fedutin, Ivan D; Steel, Debbie; Meschersky, Ilya G; Hautin, Marie; Burdin, Alexander M; Hoyt, Erich; Filatova, Olga A; Jung, Jean-Luc
Abstract: Mitochondrial DNA (mtDNA) differences between humpback whales on different feeding grounds can reflect the cultural transmission of migration destinations over generations, and therefore represent one of the very few cases of gene-culture coevolution identified in the animal kingdom. In Russian Pacific waters, photo-identification (photo-ID) studies have shown minimal interchange between whales feeding off the Commander Islands and those feeding in the Karaginsky Gulf, regions that are separated by only 500 km and have previously been lumped together as a single Russian feeding ground. Here, we assessed whether genetic differentiation exists between these 2 groups of humpback whales. We discovered a strong mtDNA differentiation between the 2 feeding sites ( F ST = 0.18, Φ ST = 0.14, P < 0.001). In contrast, nuclear DNA (nuDNA) polymorphisms, determined at 8 microsatellite loci, did not reveal any differentiation. Comparing our mtDNA results with those from a previous ocean-basin study reinforced the differences between the 2 feeding sites. Humpback whales from the Commanders appeared most similar to those of the western Gulf of Alaska and the Aleutian feeding grounds, whereas Karaginsky differed from all other North Pacific feeding grounds. Comparison to breeding grounds suggests mixed origins for the 2 feeding sites; there are likely connections between Karaginsky and the Philippines and to a lesser extent to Okinawa, Japan, whereas the Commanders are linked to the Mexican breeding grounds. The mtDNA differentiation between the Commander Islands and Karaginsky Gulf suggests a case of gene-culture coevolution, correlated to fidelity to a specific feeding site within a particular feeding ground. From a conservation perspective, our findings emphasize the importance of considering these 2 feeding sites as separate management units.